(818) Confidence Intervals for Economic Quantities Derived from Empirical Production Functions فترات الثقة للكميات الاقتصادية المستمدة من دوال الإنتاج التجريبية - Fahmi K. Bishay (INP, 2024)
The production function, originally developed by economists, is a concept drawn from physical and biological sciences. It helps in understanding the relationship between inputs and outputs, facilitating decisions that benefit producers and consumers. While economic criteria and price data are essential for decision-making, this study focuses on physical quantities derived from empirical production functions, such as marginal physical productivity, isoquants, and isoclines. These are critical for determining optimal resource allocation and production plans, yet their reliability is often overlooked. This paper aims to compute confidence regions for these estimates, providing a general and systematic approach to ensure their reliability.